Impurity induced non-bulk stacking in chemically exfoliated h-BN nanosheets. - Shmeliov, A; Kim, J; Borisenko, K; Wang, P; Okunishi, E; Shannon, M; Kirkland, A; Nellist, P; Nicolosi, V (2013)
Structural characterization of 2D nanomaterials is an important step towards their future applications. In this work we carried out imaging and structural analysis of 2D h-BN produced by chemical-exfoliation, emphasizing the stacking order in few-layer sheets. Our analysis, for the first time has shown conclusively that non-bulk stacking can exist in 2D h-BN.